A comment on the impact of the initial tax mix on the dividends of an environmental tax form - Daniel Weinbrenner (Universität Siegen, Fakultät III, Wirtschaftswissenschaften, Wirtschaftsinformatik und Wirtschaftsrecht, 1997)
The effects of an increase in an emission tax rate are analyzed. The initial tax mix of the economy is such that the higher emission rate serves to internalize social costs an simultaneously approaches a second-best tax system (in the absence of environmental distortions). It is shown that this kind of tax system as a starting point for an environmental tax reform is not sufficient to reap a clear-cut double dividend even though "unnormal" cases like a backward-bending labor supply curve and adverse revenue effects are excluded. In particular, if the wage elasticity of labor supply is positive and the tax on the clean good is relatively high compared to the tax on the dirty good an environmental tax reform may lead to an "ecological paradox", i. e. increases the demand for the dirty good because the income effects caused by the decrease of the tax rate on the clean consumption good dominate both the substitution effects of the tax rate changes and the income effect of the increased emission tax rate. Hence, there may be no environmental dividend.
Keywords: 330